Compliance with IAS/IFRS and firm characteristics: evidence from the emerging capital market of Turkey - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
The purpose of this study is to investigate the compliance level of Turkish firms with international accounting standards (IAS) and international financial reporting standards (IFRS), and to examine the factors that impact adoption level of firms to IAS/IFRS. This study is based on a comprehensive questionnaire survey about IAS/IFRS implementation of largest Turkish industrial firms, namely ICI 500. The findings and implications are important as these companies are expected to be the leading adopters of IAS/IFRS. Firstly, we determined that firms do not implement all IAS/IFRS (international accounting standards/international financial reporting standards) equally; some are used more, some less. As a second stage in the study, we tried to determine what firm characteristics impact compliance with IAS/IFRS. We found that listing status, training staff, foreign ownership, and firm size are significant determinants of IAS/IFRS compliance, whereas leverage and profitability are not.
Keywords: International accounting standards (IAS); international financial reporting standards (IFRS); compliance; Turkey; FINANCIAL-REPORTING STANDARDS; IFRS ADOPTION; DETERMINANTS; COMPANIES; RELEVANCE; AUSTRALIA